The role of grazing animals in the natural regeneration of Samanea saman in degraded pasture in the Philippines - Pasicolan, P.N.; Ramos, M.T.; Menz, K. (Australian National University, 1998)
The bioecological basis for the symbiotic relationship between grazing animals and Samanea is analysed. The contributory factors enhancing such relationships are examined, with the aim of evolving a successful reforestation model that builds on the natural process of regeneration on degraded grasslands. The study site was in the Province of Cagayan, Luzon Philippines. The methodology consisted of a series of bioecological experiments, plus a socioeconomic survey. The bioecological experiments addressed seed germination, seed digestibility and forage preference by grazing animals. A socioeconomic component is included to determine the income gains to the farmer from Samanea.